Single‐enzyme kinetics with fluorogenic substrates: lessons learnt and future directions. Issue 19 (12th June 2014) - Turunen, Petri; Rowan, Alan E.; Blank, Kerstin
Abstract : Single‐molecule fluorescence techniques have developed into powerful tools for studying the kinetics of biological reactions at the single‐molecule level. Using fluorogenic substrates, enzymatic reactions can be observed in real‐time with single‐turnover resolution. The turnover sequence contains all kinetic information, giving access to reaction substeps and dynamic processes such as fluctuations in the reaction rate. Despite their clearly proven potential, the accuracy of current measurements is limited by the availability of substrates with 1:1 stoichiometry and the signal‐to‐noise ratio of the measurement. In this review we summarize the state‐of‐the‐art and discuss these limitations using experiments performed with α‐chymotrypsin as an example. We are further providing an overview of recent efforts aimed at the improvement of fluorogenic substrates and the development of new detection schemes. These detection schemes utilize nanophotonic structures such as zero mode waveguides or nanoantennas. Nanophotonic approaches reduce the size of the effective detection volume and are a powerful strategy to increase the signal‐to‐noise ratio. We believe that a combination of improved substrates and novel detection schemes will pave the way for performing accurate single‐enzyme experiments in biologically relevant conditions.